Hubungan Riwayat Bayi Berat Lahir Rendah (BBLR) dengan Kejadian Stunting pada Balita Usia 24-59 Bulan di Desa Giripurno - Hanisa; Ernawati, Dwi (CV. CENDIKIA JENIUS INDONESIA, 2024)
Stunting is one of the most challenging health problems in Indonesia that can affect the functional and physical condition of children's bodies, as well as increase the morbidity rate of children. In 2023, 19.13% of stunting cases occurred in Giripurno Village. This research was carried out in Giripurno Village on 17 November 2023. This study aims to determine the correlation between the history of low birth weight babies and the incidence of stunting in children aged 24-59 months in Giripurno Village. The research employed quantitative method, with an analytic survey research design. The research design used in this study was case control with a retrospective approach. The sampling technique was purposive sampling technique with 68 samples and a ratio of 1:1. Data collection used observation sheets and data analysis used chi-square test. The results showed the incidence of LBW in children aged 24-59 months in Giripurno Village was 25%. The results of the analysis using the chi-square test obtained a p-value of 0.002 and OR 7.233 which showed there was a correlation between low birth weight babies and the incidence of stunting in children aged 24-59 months in Giripurno Village. In conclusion, toddlers who suffer from low birth weight have a 7.233 greater risk of stunting than toddlers who do not experience LBW. It is recommended for mothers to provide nutritious nutritional intake to toddlers.